Genetic differentiation of dengue vector Aedes aegypti in the small geographical scale of Banyumas District, Indonesia based on Cytochrome Oxidase I - Mohammed A. Mohammed; Agus Nuryanto; Endang Srimurni K Kusmintarsih (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mohammed MA, Nuryanto A, Kusmintarsih ES. 2021. Genetic differentiation of dengue vector Aedes aegypti in the small geographical scale of Banyumas District, Indonesia based on Cytochrome Oxidase I. Biodiversitas 22: 675-683. Aedes aegypti (Linnaeus, 1762) is a major vector of arboviruses. Currently, Ae. aegypti is spreading throughout the Banyumas District, Central Java, Indonesia and there is little information regarding the genetic variation of this species, yet the information is essential to develop effective vector control measures. The aims of this study was to evaluate the genetic differentiation of Ae. aegypti populations in South Purwokerto and Cilongok subdistricts. Mosquito larvae were collected using oviposition traps inside houses in South Purwokerto and Cilongok (Jastaba village). Twenty larvae of Ae. aegypti, ten from each location were identified and used for genetic analysis. Analysis of mitochondrial cytochrome Oxidase I (mtCOI) produced around 600 bp fragments, detecting ten haplotypes. The haplotype diversity and nucleotide diversity indices were higher in South Purwokerto samples. Tajima and Fu’s statistics indicated that the sampled populations were in genetic equilibrium. Indices of demographic history were fit for a spatial expansion model. Higher genetic variation was observed within the population compared to between the populations. Furthermore, strong genetic difference was detected between the two populations, with highly significant FS (p < 0.0001). Weak haplotype sharing occurred between the two populations assuming that the gene flow was facilitated by human transportation. All haplotypes were a cluster of single clades and closely related to haplotypes generated from previous studies in Central Java.